+0  
 
0
57
1
avatar+175 

given f(x)= -3-x^2

 

find and simplify the quotient = f(a+h)-f(a-h)/h

 Dec 16, 2019
 #1
avatar+106519 
+1

 

 

Here goes  nothing  !!!

 

[ - 3 - ( a + h)^2  ]  -  [ -3 - (a -h)^2  ]

_____________________________   =

                  h

 

[ -3 - ( a^2 + 2ah + h)^2 ]  - [ -3 - (a^2 - 2ah + h^2)  ]

__________________________________________   =

                       h

 

[-3 - a^2 - 2ah - h^2    - [ -3 - a^2 + 2ah -  h^2  ]

________________________________________  =

                        h

 

[ -3 -a^2 -2ah - h^2   + 3 + a^2 - 2ah  + h^2 ]

_______________________________________   =

                         h

 

- 4ah

____   =

   h

 

 

-4a

 

 

 

cool cool cool

 Dec 16, 2019

3 Online Users